It's All Good: Corporate Social Responsibility Reduces Negative and Promotes Positive Responses to Service Failures among Value-Aligned Customers. (April 2015) - Joireman, Jeff; Smith, Dustin; Liu, Richie L.; Arthurs, Jonathan
The present research investigates whether corporate social responsibility (CSR) reduces negative and promotes positive responses to service failures among value-aligned customers. Study 1 shows that customers are less likely to experience anger and spread negative word of mouth following a service failure when a firm engages in high (donating 15% of profits to environmental conservation) but not low (donating 2% of profits) levels of environmental CSR, but only if customers are high in environmental concern. In Study 2, the authors explore the benefits of CSR policies that target a broader range of beneficiaries versus policies that offer customers a choice over the firm's CSR allocations. Compared with a no-CSR policy, CSR with choice has a stronger effect on customers' emotions and intentions by enhancing perceived value alignment, reducing anger and regret over choosing the firm, and increasing guilt over harming the firm. These emotions subsequently reduce negative word of mouth and increase positive word of mouth and repurchase intentions. The results support the benefits of value-aligned and choice-based CSR policies in the wake of service failures.